2021
DOI: 10.1111/ceo.13951
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of complications and visual outcomes between big‐bubble deep anterior lamellar keratoplasty and penetrating keratoplasty for fungal keratitis

Abstract: Background To compare the postoperative complications and visual outcomes of big‐bubble deep anterior lamellar keratoplasty (BB‐DALK) and penetrating keratoplasty (PK) for fungal keratitis (FK). Methods This retrospective study included 94 cases of BB‐DALK for FK and 161 cases of PK for FK from a tertiary ophthalmology care centre. Results The most common FK pathogens were Fusarium (n = 84, 32.9%) and Aspergillus (n = 67, 26.3%). The recurrence rates after BB‐DALK and PK were 3.2 and 5%, respectively (p = 0.72… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 26 publications
(41 reference statements)
1
11
0
1
Order By: Relevance
“…Lamellar keratoplasty (LK) as an alternative surgical intervention to treat fungal keratoplasty has been reported in the literature [ 105 , 106 , 107 , 108 , 109 ]. Unlike TPK, which is most frequently performed for perforations (either impending or frank), in the context of FK, lamellar keratoplasty is usually performed to surgically resect infections not extending into the anterior chamber.…”
Section: Surgical Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Lamellar keratoplasty (LK) as an alternative surgical intervention to treat fungal keratoplasty has been reported in the literature [ 105 , 106 , 107 , 108 , 109 ]. Unlike TPK, which is most frequently performed for perforations (either impending or frank), in the context of FK, lamellar keratoplasty is usually performed to surgically resect infections not extending into the anterior chamber.…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…LK has been compared to TPK in two retrospective studies for fungal keratitis [ 105 , 115 ]. An early study from India in the 1960s concluded that “lamellar keratoplasty invariably fails, because the fungus is able to penetrate Descemet’s membrane” after it found that 6/7 LK cases developed re-infection, compared to only 1/10 cases in the TPK group [ 115 ].…”
Section: Surgical Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Deep anterior lamellar keratoplasty is slowly becoming a popular option for repairing descemetoceles and perforations. Visual outcomes appear comparable with penetrating keratoplasty with decreased risk for secondary glaucoma and graft rejection [78,79]. However, there is concern for higher reinfection risk due to retained infectious material or infectious seeding of the anterior chamber by Descemet membrane rupture [78,80].…”
Section: Procedural and Surgical Therapiesmentioning
confidence: 99%
“…8 Although deep anterior lamellar keratoplasty (DALK) is an alternative to full-thickness penetrating keratoplasty in patients with anterior corneal disorders and a healthy endothelium and has been shown to offer several advantages, namely, better long-term graft survival, minimal steroid-related complications, no risk of endothelial rejection, and avoidance of open sky surgery, there is a paucity of peer-reviewed literature on long-term follow-up studies of patients with MPS having undergone successful DALK. [9][10][11][12][13][14][15][16][17][18] This study aims to describe the long-term outcomes of patients with MPS type I who have undergone DALK surgery.…”
mentioning
confidence: 99%